Activity of Zearalenone in the Porcine Intestinal Tract - Gajęcka, Magdalena (Molecules, 2016)
This study demonstrates that low doses (somewhat above the No Observed Adverse Effect Level, NOAEL) of the mycoestrogen zearalenone (ZEN) and its metabolites display multispecificity towards various biological targets in gilts. The observed responses in gilts were surprising. The presence of ZEN and zearalenols (ZELs) did not evoke a response in the porcine gastrointestinal tract, which was attributed to dietary tolerance. Lymphocyte proliferation was intensified in jejunal mesenteric lymph nodes, and lymphocyte counts increased in the jejunal epithelium with time of exposure. In the distal digestive tract, fecal bacterial counts decreased, the activity of fecal bacterial enzymes and lactic acid bacteria increased, and cecal water was characterized by higher genotoxicity. The accompanying hyperestrogenism led to changes in mRNA activity of selected enzymes (cytochrome P450, hydroxysteroid dehydrogenases, nitric oxide synthases) and receptors (estrogen and progesterone receptors), and it stimulated post-translational modifications which play an important role in non-genomic mechanisms of signal transmission. Hyperestrogenism influences the regulation of the host’s steroid hormones (estron, estradiol and progesteron), it affects the virulence of bacterial genes encoding bacterial hydroxysteroid dehydrogenases (HSDs), and it participates in detoxification processes by slowing down intestinal activity, provoking energy deficits and promoting antiporter activity at the level of enterocytes. In most cases, hyperestrogenism fulfils all of the above roles. The results of this study indicate that low doses of ZEN alleviate inflammatory processes in the digestive system, in particular in the proximal and distal intestinal tract, and increase body weight gains in gilts.